Exploring the relationship between customer’s experience and customers’ re-patronage intention - Azila Jaini; Nor Asma Ahmad; Siti Zamanira Mat Zaib; Zaminor Zamzamir@Zamzamin (Faculty of Entrepreneurship and Business,UMK, 2015)
In the global competition nowadays, customer experience becomes a new focus for every business owner. Repeat customers are of paramount importance for it to ensures continuous business growth of the firm and hence, business profitability. The purpose of this study is to examine the relationship between customers experience and repeat patronage (re-patronage) intention among existing customers. The study was conducted quantitatively, in which convenience sampling method was chosen in collecting data at chosen local fast-food restaurants. 289 questionnaires were collected and the findings were analysed using Predictive Analytics Software (PASW) version 21.0. The results show that positive experience faced by customers will develop memorable moments and increase their intention to make a repeat purchase/dining at their favorable restaurants. Overall, this study suggested that a fast food restaurant should focus on its delivering services to the customers and simultaneously enhancing the other qualities in order to capture long-term relation with customers.